Swing-up and Stabilization Control of Rotary Inverted Pendulum by using LQR-based ANFIS - Tran, Minh Đức; Vo, Minh Tài; Pham, Quang Minh; Nguyen, Đức Trung; Vo, Hữu Thống; Tran , Nho Thể; Le , Đình Đạt; Nguyen, Lê Vương; Tran, An Khang; Phan, Cao Hoàng (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
RIP is a SIMO nonlinear system which has simple mechanical structure but high nonlinear level. This is a popular model in laboratories of control automation. In this paper, we present an ANFIS network which is developed from a former LQR controller in stabilizing system at equilibrium point– upright position. In addition, an energy swing-up controller is designed and tested in this paper. Simulation and experimental results in this paper prove the abilities of these methods in balancing RIP model.